UKSESI MIKROBA DAN ASPEK BIOKIMIAWI FERMENTASI MANDAI DENGAN KADAR GARAM RENDAH - Nur, Hasrul Satria (Makara Journal of Science, 2009)
Microbial succession and biochemical aspects of mandai fermentation at low salt concentration. Mandai is fermented food that traditionally made from the flesh of jack fruit (Arthocarphus champeden Spreg.). Usually mandai is made as high salt concentration. However, the objective of this research is to study the succession and biochemical aspects of microbials during fermentation at low salt concentration (10% w/v) for 14 days. During the period of fermentation microbial cell numbers and biochemical aspects were observed at the 3rd, 5th, 7th and 14th day. Total cell number of bacteria and yeast were measured by pour plate method. The measurement was also conducted on flesh before incubation. The biochemical aspect observation included the contents of reducing sugar, N-total, salt, and pH. The research results indicated that the pattern of microbial succession occurred the fermentation. Yeast cells grew dominantly (2.8 x 109 CFU/g) on the 5th day fermentation but bacteria were dominant at the end (1.1 x 107 CFU/g). The highest decrease of reducing sugar and N-total contents were 0.240% at the 14th day and 0.159% at the 5th day, respectively. However, salt concentration was relatively stable and pH was varied within the range of 3.71-6.12 for the whole period fermentation.